HOW SUPPLY CHAIN DISRUPTIONS AFFECT THE WAY COMPANIES FUNCTION – A CASE STUDY ON THE EXAMPLE OF THE TFL ENTITY GEIS GLOBAL LOGISTICS - Bukowska-Piesztrzyńska, Agnieszka; Golec, Paweł; Motowidlak, Urszula (Management and Administration Journal, 2024)
The aim of the article is to present the essence of disruptions in the supply chain and assess how they are linked with enterprise resilience. Furthermore, it aims to indicate how company’s operations are impacted in the long term. The article has a theoretical and empirical character. It presents the results of empirical research conducted in the third quarter of 2022 at Geis Global Logistics. Here we look to answer three research questions concerning the problems and challenges resulting from the pandemic and geopolitical crisis, their role in creating new development opportunities for the company, and defining key logistics and supply chain strategies to maintain its competitiveness in a turbulent environment. The results show the actions taken by the Transport Forwarding Logistics (TFL) industry entity to survive and be competitive in the market, i.e., building resilience through the ability to absorb, react, and rebuild after disruptions.